Studi Kontraksi Tugas dan Fungsi Hakim di Pengadilan Agama - Syaiful Hidayat (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2016)
A Judge is a key element in the trial. In fact he was identical to the court itself. Similarly, the decision of the court identified with the judge's decision. Therefore, law enforcement and justice lies in the ability of judges in formulating decisions that reflect fairness. With regard to the duties and functions of the judge, in this case the trial judge Religion in Indonesia, which is one element of the law enforcement component directly involved with the legal process will be faced with a dilemma problem. On the one hand, the religious court judge must hold to Irish law. While on the other hand, the religious court judges must take into account the level of public awareness of the legal instruments. In addition, for the assurance of the process of law enforcement, religious court judges are also faced with a problem that dilemma. Because of the involvement of the religious court judges against one of the instruments carried to excess can lead to deviations of the purposes of the law itself, which is justice